2016
DOI: 10.1097/bot.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femoral Replacement for Acute Distal Femoral Fractures in Elderly Patients

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 26 publications
3
64
1
4
Order By: Relevance
“…reported on a group of 18 patients treated with DFR for native distal femur fracture and had 2 complications including one femur fracture requiring revision and one early infection that was successfully treated with revision of components. In this study, all patients were either very or extremely satisfied at the average follow-up of 2.3 years [6] . Rosen and Strauss reported on 24 patients treated with DFR for primary distal femur fracture and had no complications at mean follow-up of 11 months, with 71% returning to preoperative ambulatory function [12] .…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…reported on a group of 18 patients treated with DFR for native distal femur fracture and had 2 complications including one femur fracture requiring revision and one early infection that was successfully treated with revision of components. In this study, all patients were either very or extremely satisfied at the average follow-up of 2.3 years [6] . Rosen and Strauss reported on 24 patients treated with DFR for primary distal femur fracture and had no complications at mean follow-up of 11 months, with 71% returning to preoperative ambulatory function [12] .…”
Section: Discussionmentioning
confidence: 78%
“…Rosen and Strauss reported on 24 patients treated with DFR for primary distal femur fracture and had no complications at mean follow-up of 11 months, with 71% returning to preoperative ambulatory function [12] . These studies concluded that DFR is a viable treatment option for elderly patients with comminuted intraarticular distal femur fractures with preexisting arthrosis that allows for immediate weight-bearing, with most patients returning to preoperative functional status at baseline [6] , [12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the latter case, treatment has often involved megaprostheses with a metallic replacement of the distal femur or allograft replacement of the distal femur [4] , [8] . The disadvantage of these techniques are associated with the low level of biological reconstruction and the high risk of infection that results from the large metallic or dead bone surfaces [8] , [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%